Problematika Pengintegrasian Pembelajaran Tematik IPS dalam Penguatan Pendidikan Karakter di Sekolah Dasar - Nabella Yaniariza Putri; Septi Yunita; Tin Rustini (Journal on Education, 2022)
The integration of subjects in the 2013 curriculum, in addition to producing many new innovations in learning, also has other impacts, namely limited teaching materials. The limitation of learning materials, especially social studies learning, is due to the impact of the integration that appears so that the main content to the supporters in the material is not delivered optimally. Social studies learning which is not only learning about general material but also about attitude development must be realized to the maximum. This will have an impact on the character development of students expected in social studies learning itself. This research is motivated by the problems that arise in integrating social studies learning, especially in strengthening student character education. This study aims to provide an overview of the attitudes that can be done by teachers and students in minimizing the impact that occurs due to the integration of social studies learning. In making this article, we used a qualitative approach by studying literature based on several scientific journals, electronic books, and other sources that have been confirmed for accuracy. The results of this study describe that there are several efforts that can be made by teachers in developing social studies thematic learning and strengthening character education.